Ideal TPACK For Arabic Language Lecturer: Student Voices - Rozak, Abd.; Nisa, Pia Khoirotun; Albantani, Azkia Muharom (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
TPACK-based learning (Technology Pedagogical Content Knowledge) is an alternative strategy in the online-based learning process. This has an impact on the selection of learning activities, media as well as improving the quality of teaching pedagogy, so it is necessary to map the TPACK learning process based on the students’ perceptions who have participated in the TPACK-based learning Arabic. This study aims to identify student responses to the TPACK-based learning process with several categories. This study uses an exploratory research design by adopting questionnaire consisting of 27 statement items covering the 7 TPACK sub-domains. The questions were distributed via google form to 129 students, the analysis applied descriptive statistical techniques. The research findings show that the implementation of Arabic learning based on TPACK framework utilise indicators such as the use of online media, the application of online-based classroom administration, the availability of online learning resources, and the improvement of teaching pedagogy based on teaching technology. Through the integration of technology, pedagogy, content knowledge, it can accelerate the process of acquiring and increasing student Arabic productivity. This study recommends further research to identify the application and effectiveness of using technology, content and pedagogy separately.